The Implications of The Covid-19 Pandemic on The Utilization and Catastrophic Costs of National Health Insurance - Wahyu Pudji Nugraheni; Syarifah Nuraini; Risky Kusuma Hartono (Health Science Journal of Indonesia, 2022)
Background: The COVID-19 pandemic in Indonesia has significantly impacted the health care system and insurance schemes. Social distancing policies during the pandemic have led to changes in utilization in health facilities, especially those related to catastrophic diseases that cost a lot of money. This study aims to analyse the impact of the Covid-19 pandemic on the utilization and financing of catastrophic diseases in the National Health Insurance (NHI) program. Methods: The research design is quantitatively and qualitatively. The quantitative study analysed secondary data obtained from the Social Security Administrator for Health and the nat. This study also has qualitative data from in-depth interviews with government and private hospital informants, health economists, and social health insurance experts. Results: COVID-19 pandemic has impacted decreasing the utilization of National Health Insurance participants to health facilities and significantly affecting the financing of catastrophic diseases. Before pandemic, the disease with the highest claim fee was ischemic heart disease, and after the pandemic, the disease with the highest claim fee was chronic kidney disease. There is also a change in the ranking diseases pattern before and during the covid-19 pandemic. Conclusion: In the future, National Health Insurance financing needs to expand the scope of the benefits of preventive and promotive services, especially the prevention of catastrophic diseases, to reduce the burden of NHI claims. Health facilities provided by National Health Insurance providers need to prepare for better management of health services after the pandemic.